Synthesis and characterization of Cadmium (II) complex with tetradentate N2O2- donor Schiff base and biological activity - Patra, Animesh; Sahoo, Gobinda Prasad; Setua, Palash; Pandey, Akhil; Maiti, Surajit (International Journal of Scientific Research in Biological Sciences, 2019)
Transition metal complex of Cd (II) with tetradentate schiff base derived from the condensation of 4-nitro-1,2-diamino benzene and 5-nitro-salicyldehyde (H2L) have been synthesized. The synthesized square planar complex was investigated using elemental analysis (C, H and N), infrared, conductivity and electronic spectroscopic tools. The interactions of cadmium (II) complex examined towards Bovine serum albumin (BSA) with the help of absorption and fluorescence spectroscopic tools. The complex is strongly binds to proteins, then we study the antibacterial activity of the Schiff base and its cadmium complex by agar disc diffusion method against some species of pathogenic bacteria (Escherichia coli, Vibrio cholerae, Streptococcus pneumonia and Bacillus cereus).The result indicated that cadmium complex was more activity than ligand due to higher lipophilicity effect.